Performance Evaluation of Five Selected Indonesian Banks Using Data Envelopment Analysis - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This paper employs Data Envelopment Analysis (DEA) to evaluate the operational performance of a bank relative to the performance of its peer banks. Utilizing  financial data from the year 2005 to 2007 of five selected leading Indonesia’s banks to conduct the analysis, the use of DEA yields the following: 1) rankings of  DMUs using efficiency scores, 2) establishment of the reference group against which a DMU is evaluated, and 3) identification of areas of deficiency. Nine of the 15 DMUs were found to be in need of improvements. In addition to identifying best-practice banks and those that are out-of-line with the best practice banks, DEA also points to the specific changes that must be made in the less productive branches in order for them to catch up with their best practice peer group. The findings of this study should help management in identifying the strengths and weaknesses of their banks.